The Development of Physics Learning Module Based on Creative Thinking - Desi Widyaningsih Ahmad; Muhammad Arsyad; Helmi Helmi (Jurnal Pendidikan Fisika, 2021)
The objectives of this study are (i) analyzing the profile of the Physics learning module based on creative thinking; (ii) analyzing the teachers'/practitioners' responses toward the development of Physics learning module based on creative thinking; (iii) finding out the improvement of learning outcomes by using the Physics learning module based on creative thinking. The subject of this study was 30 students of XI MIA 2 of SMAN 1 Campalagian. This study employed the Research and Development method using the ADDIE (Analysis, Design, Development, Implementation, and Evaluation) model. Observation, interview, and questionnaire were used to collect the data. The result of the study showed that the Physics learning module based on creative thinking was valid based on expert validation through the Gregory test so that this module is feasible to use. The results of the responses of 30 students and 4 teachers were in “good” category. Moreover, the students' learning outcomes increased after using Physics learning module based on creative thinking. This can be seen from the value of the posttest result that was higher than the pretest result. The average N-gain value obtained was 0.51 and this value was in the medium category (0.3 g 0.7). Therefore, it can be implied that the physics learning module based on creative thinking is one of the effective learning resources used to develop students’ creative thinking skills, especially fluency, flexibility, originality, and elaborative thinking on the materials of mechanical waves, traveling waves, and stationary waves.